YES Problem: strict: b(c(a(x1))) -> d(d(x1)) b(x1) -> c(c(x1)) a(a(x1)) -> a(c(b(a(x1)))) weak: a(b(x1)) -> d(x1) d(x1) -> a(b(x1)) Proof: String Reversal Processor: strict: a(c(b(x1))) -> d(d(x1)) b(x1) -> c(c(x1)) a(a(x1)) -> a(b(c(a(x1)))) weak: b(a(x1)) -> d(x1) d(x1) -> b(a(x1)) Matrix Interpretation Processor: dim=3 interpretation: [1 0 0] [c](x0) = [0 0 2]x0 [0 0 0] , [2 2 0] [1] [d](x0) = [0 0 0]x0 + [1] [2 2 0] [3], [2 2 0] [0] [a](x0) = [0 0 0]x0 + [2] [0 2 0] [3], [1 0 0] [1] [b](x0) = [0 0 0]x0 + [1] [1 1 0] [1] orientation: [6 4 0] [6] [4 4 0] [5] a(c(b(x1))) = [0 0 0]x1 + [2] >= [0 0 0]x1 + [1] = d(d(x1)) [4 4 0] [7] [4 4 0] [7] [1 0 0] [1] [1 0 0] b(x1) = [0 0 0]x1 + [1] >= [0 0 0]x1 = c(c(x1)) [1 1 0] [1] [0 0 0] [4 4 0] [4] [4 4 0] [4] a(a(x1)) = [0 0 0]x1 + [2] >= [0 0 0]x1 + [2] = a(b(c(a(x1)))) [0 0 0] [7] [0 0 0] [5] [2 2 0] [1] [2 2 0] [1] b(a(x1)) = [0 0 0]x1 + [1] >= [0 0 0]x1 + [1] = d(x1) [2 2 0] [3] [2 2 0] [3] [2 2 0] [1] [2 2 0] [1] d(x1) = [0 0 0]x1 + [1] >= [0 0 0]x1 + [1] = b(a(x1)) [2 2 0] [3] [2 2 0] [3] problem: strict: a(a(x1)) -> a(b(c(a(x1)))) weak: b(a(x1)) -> d(x1) d(x1) -> b(a(x1)) Matrix Interpretation Processor: dim=2 interpretation: [1] [c](x0) = x0 + [0], [1 1] [d](x0) = [0 0]x0, [1 1] [0] [a](x0) = [0 0]x0 + [2], [1 0] [b](x0) = [0 0]x0 orientation: [1 1] [2] [1 1] [1] a(a(x1)) = [0 0]x1 + [2] >= [0 0]x1 + [2] = a(b(c(a(x1)))) [1 1] [1 1] b(a(x1)) = [0 0]x1 >= [0 0]x1 = d(x1) [1 1] [1 1] d(x1) = [0 0]x1 >= [0 0]x1 = b(a(x1)) problem: strict: weak: b(a(x1)) -> d(x1) d(x1) -> b(a(x1)) Qed